STABILISASI DIMENSI KAYU DENGAN APLIKASI PARAFIN CAIR - . Syahidah; Tekat Dwi Cahyono (Forestry Faculty of Universitas Hasanuddin, 2008)
Wood is a special material which can swell and shrink with the change of environmental humidity. The aim of this research was to enhance the dimensional stability of wood. Clear specimens of jackfruit wood (Artocarpus heterophyllus) ) measuring 15 cm (L) x 2 cm (R) x 2 cm (T) and mangium wood (Acacia mangium Wild.) measuring 5 cm (L) x 5 cm (R) x 5 cm (T) were prepared for treatment. The samples were firstly soaked in a liquid paraffin with 0% concentration (100% kerosene soluble), 33.3 %, 66,6% and 100%. All samples were then vacuumed for 1 hour and soaked in water for 24 hours. Results indicated that the best response for dimensional stability was performed by mangium with 33% paraffin and jackfruit wood with 66% paraffine. In addition, moisture content of all treated samples decreased after treatment. This research also showed that the treatment had no significant effect to MOE, MOR and hardness of the wood. Key words: Dimensional stability of wood, liquid parafin, mangium, jackfruit wood References